Dynamic Capabilities and Entrepreneurship-Based Pesantren Agenda in Responding to Change for Innovation Performance - Setiawan, Heri Cahyo Bagus; Fatimah, Nuzulul (Dimar : Jurnal Pengabdian Masyarakat, 2024)
The dynamic capabilities component in shaping the environment is adjusting and includes essential entrepreneurial characteristics. Organizations with dynamic, solid capabilities adapt to the business ecosystem and proactively shape it through innovation and collaboration with various parties. Based on the literature review that the author has reviewed, this study highlights the relationship between dynamic capabilities and the agenda of entrepreneurship-based pesantren in facing change. The focus is on how entrepreneurship-based pesantren can respond to change through innovative performance driven by dynamic capabilities. The research methods used are literature study and explorative qualitative. The research findings show that Pesantren's two main goals in responding to change are improving their innovative performance. First is developing adaptive and creative capabilities as an agenda of change for creating dynamic pesantren entrepreneurship. Second, there is a strong relationship between dynamic capacity as the main agenda of entrepreneurship-based pesantren in East Java in improving innovative performance, which is supported by the involvement of Human Resources of santri and Kiai in the management of entrepreneurship-based pesantren. The results of this study are expected to provide theoretical contributions and directions for future research.